Ideation, concretion and performance in architecture. The “Garden Social El Porvenir” project of Giancarlo Mazzanti (REVISTA NODO, 2014)
Through a case study, the authors tested a research approach in which the implicit knowledge in the good professional practice is potentiated through a critical exercise mediated by theory, the experience of architecture and some qualitative research techniques. The case study is the “Social Garden El Porvenir” project from the architect Giancarlo Mazzanti, which is presented through a synthesis of its ideation process, its concretion and an analysis of its performance assessed through advanced research techniques, complemented by the experience of visiting the building. As conclusion, this exercise shows the validity of a architectural research model in which through studies based on the notion of “iterative loop” proposed by researcher Jeremy Till, is possible to obtain knowledge that feed back the various processes of architectural production
Keywords: Iterative loop; research in architecture; architectural practice; production processes; processes of reception